Total Amino Acids by UHPLC–UV in Infant Formulas and Adult Nutritionals, First Action 2018.06. (3rd December 2019) - Jaudzems, Greg; Guthrie, Joseph; Lahrichi, Sabine; Fuerer, Christophe
Abstract: Background: An acid hydrolysis ultrahigh-performance LC–UV method was evaluated for the determination of total amino acids in infant formula and adult/pediatric nutritional formula. Objective: It was assessed for compliance against AOAC INTERNATIONAL Standard Method Performance Requirements (SMPR ® ) established by the Stakeholder Panel for Infant Formula and Adult Nutritionals (SPIFAN). Methods: A single-laboratory validation (SLV) study was conducted as a first step in the process to validate the method. In this SLV, 17 SPIFAN matrices representing a range of infant formula and adult nutritional products were evaluated for their amino acid content. Results: The analytical range was found to be within the needs for all products; some may require a dilution. Evaluation of trueness performed on Standard Reference Material 1849a (Infant/Adult Nutritional Formula) showed all compounds met the SMPR theoretical value, with exceptions for threonine and tyrosine. These may have a bias for the National Institute of Standards and Technology (NIST) data, depending on hydrolysis used in the determination of the NIST certificate of analysis. Conclusions: Based on the results of this SLV, this method met the SMPR and was approved as a First Action method by the AOAC Expert Review Panel on Nutrient Methods on August 28, 2018.